Memory CD8+ T cell compartment associated with delayed onset of Plasmodium falciparum infection and better parasite control in sickle‐cell trait children. Issue 3 (19th March 2021) - Loiseau, Claire; Traore, Boubacar; Ongoiba, Aissata; Kayentao, Kassoum; Doumbo, Safiatou; Doumtabe, Didier; de Sousa, Karina P; Brady, Jamie L; Proietti, Carla; Crompton, Peter D; Doolan, Denise L
Abstract: Objectives: Study of individuals with protection from Plasmodium falciparum ( Pf ) infection and clinical malaria, including individuals affected by the sickle‐cell trait (HbAS), offers the potential to identify cellular targets that could be translated for therapeutic development. We previously reported the first involvement of cellular immunity in HbAS‐associated relative protection and identified a novel subset of memory‐activated NK cells that was enriched in HbAS children and associated with parasite control. We hypothesised that other memory cell subsets might distinguish the baseline profile of HbAS children and children with normal haemoglobin (HbAA). Methods: Subsets of memory T cells and NK cells were analysed by flow cytometry in paired samples collected from HbAS and HbAA children, at baseline and during the first malaria episode of the ensuing transmission season. Correlations between cell frequencies and features of HbAS‐mediated protection from malaria were determined. Results: HbAS children displayed significantly higher frequency of memory CD8 + T cells at baseline than HbAA children. Baseline frequency of memory CD8 + T cells correlated with features of HbAS‐mediated protection from malaria. Exploration of memory CD8 + T cell subsets revealed that central memory CD8 + T cell frequency was higher in HbAS children than in HbAA children. Conclusion: This study shows that HbAS children develop a larger memory CD8 + T cell compartment than HbAA children, and associates this compartment with better control of subsequent onset of infection and parasite density. Our data suggest that central memory CD8 + T cells may play an important role in the relative protection against malaria experienced by HbAS individuals, and further work to investigate this is warranted. Abstract : The sickle‐cell trait is associated with protection against malaria, but the role of host immunity has been poorly explored. In this study, we show that central memory CD8 + T cells are associated with control of infection and parasite density in sickle‐cell individuals, by analyzing T cell and NK cell subsets in individuals with or without the sickle‐cell trait prior to and at the time of clinical malaria.